2019
DOI: 10.18621/eurj.423324
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hospital ethical climate on the nurses' moral sensitivity

Abstract: Objectives:The study determines the effects of the hospitals ethical climate on the moral sensitivity of nurses. Methods: The study design is descriptive and correlational. The data was obtained from 99 nurses who voluntarily accepted to fully participate in the surveys conducted. The data was analysed using descriptive statistics and Pearson correlations. Results: As a result of the study, the ethical climate perception of nurses and their moral sensitivity level was found to be above average. A positive, mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 27 publications
3
38
0
3
Order By: Relevance
“…In line with our study, Barimani et al concluded that ethical climate was favorable. ( 16 ) In other studies, nurses also believed that ethical climate in their hospital was above average ( 11 ) and moderate. ( 17 ).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In line with our study, Barimani et al concluded that ethical climate was favorable. ( 16 ) In other studies, nurses also believed that ethical climate in their hospital was above average ( 11 ) and moderate. ( 17 ).…”
Section: Discussionmentioning
confidence: 95%
“…(26) However, Elçi et al (2015) found out that ethical climate had no effect on job burnout in financial services workers. (27) Mulki et al (10) and Minamizono et al (28) found out that ethical climate affects the intention to leave, and a positive significant relationship was found between nurse's hospital climate perception and their moral sensitivity (11) and performance. (29) Unfavorable ethical climate seems to increase job dissatisfaction, stress, burnout, and intentions to leave the job followed by reduced quality of caring services and prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Araştırmada ahlaki duyarlılık alt boyutlarından sadece bütüncül yaklaşım ve toplam ADA ile hemşirelerin İD düzeyi arasında pozitif, anlamlı ve çok zayıf bir ilişki olduğu belirlenmiştir. Etik karar verebilme becerisini kullanmada ahlaki duyarlılık önemli bir etkiye sahiptir (41). Ahlaki duyarlılık hastanın gereksinimini saptamak için bakım verenin farkındalığını, sözel ve sözel olmayan belirtileri ve davranışları anlama becerisini gerektirir (42).…”
Section: Tablo 4 Hemşirelerin Ahlaki Duyarlılığı Ile Etik Karar Verebilme Düzeyi Arasındaki Korelasyon Analiziunclassified
“…Ethical climate is a component of organizational climate and as a part of organization character, represents ethics in the organization [24,25].Ethical standards in organization promote respect and honesty among personnel and increase job satisfaction and organizational success [23].…”
Section: Introductionmentioning
confidence: 99%